Analisis Pengaruh Kepercayaan dan Pelayanan Terhadap Minat Usaha Mikro, Kecil, dan Menengah (UMKM) Mengajukan Pembiayaan di Bank Syariah : (Studi Kasus Pengusaha Mikro Pasar Bawah Bukittingi) - Nur Hasimah; Andis Febrian (Universitas 17 Agustus 1945 Semarang, 2024)
This research is motivated by the importance of trust and service in the interest of micro, small and medium enterprises (MSMEs) to apply for financing at sharia banks. This research aims to find out and analyze how much influence trust and service have on the interest of micro, small and medium enterprises (MSMEs) to apply for financing at sharia banks. This research uses a correlational method with a quantitative approach. Sampling used purposive sampling. The data used is primary data and secondary data. Primary data was obtained from respondents through distributing questionnaires, while secondary data was based on observations, journals, articles and previous research. Meanwhile, multiple linear regression analysis techniques. Test classical assumptions, and test hypotheses. Analysis of this research using SPSS, based on research results at a significance level of 5% shows that. (1). Trust has a significant effect on business interest, the results of the regression coefficient are 0.122 and based on the test results of the coefficient of determination of the trust variable on business interest, it is 0.324 or 32.4% and has a significant level of (0.001 ≥ 0.05). (2) service has a significant effect on business interest, the results of the regression coefficient are 0.324 and based on the test results of the coefficient of determination of the trust variable on business interest, it is 0.324 or 32.4% and has a significant level of (0.001 ≥ 0.05). (3) the influence of trust and service has a positive F_count value of 43.368 which is greater than F_table 3.107 with a significance level of 0.000 ≤ 0.05 and a coefficient of determination test result of 0.324% or 32.4%. So it can be concluded that the trust and service variables influence business interest by 32.4% and the remaining 67.6% is influenced by other variables.